CAREGIVING IN CANCER: THE DUAL PATH OF STRESS AND GROWTH - Rabab Amakhchoune; Fadoua Bousalama (PEOPLE: International Journal of Social Sciences, 2025)
This study utilized a quantitative approach to examine the relationship between social support and the experiences of stress and growth among caregivers of cancer patients in Morocco. Employing a cross-sectional design, data were gathered from caregivers using validated measures of perceived stress, social support, and post-traumatic growth. Regression analyses demonstrated that higher levels of emotional and instrumental social support were significantly associated with reduced stress and increased post-traumatic growth among caregivers. These findings highlight the protective role of strong social support networks in alleviating caregiving stress and fostering positive psychological outcomes. The study underscores the need for interventions aimed at strengthening social support systems for caregivers, particularly within the Moroccan context, where cultural and social dynamics play a significant role in caregiving experiences.